PERGESERAN RIMA DALAM PUISI TERJEMAHAN TAUFIQ ISMAIL (Rhyme Shift in Poems Translated by Taufiq Ismail) - Retno Hendrastuti (Kantor Bahasa Sulawesi Tenggara, 2017)
One of indications of the success in poetry translation is source language (SL) rhyme and meaning can be transferred into target language (TL) simultaneously. However, sometimes rhyme translation shift cannot be avoided to keep the meaning of SL. This is a qualitative descriptive research that aims to explore rhyme shift and its effect toward translation meaning accuracy. The data were SL-TL rhymes pairs found in eight poems translated by Taufiq Ismail. The analysis result showed that there were various rhyme shifts, including fixed rhymes, partial shift rhymes, and full shift rhymes. Accurate rhyme shifts (without any type rhyme shift) happens on more than a half of entire data. The shifts found were not influence the accuracy of poem meaning. Basically, those were developed as an effort to preserve poems message as a part of universal literature piece.